Vulnerability of the Great Barrier Reef to climate change and local pressures - Nicholas H. Wolff; Peter J. Mumby; Michelle Devlin; Kenneth R. N. Anthony (Global Change Biology, 2018)
Australia's Great Barrier Reef ( GBR ) is under pressure from a suite of stressors including cyclones, crown‐of‐thorns starfish ( COTS ), nutrients from river run‐off and warming events that drive mass coral bleaching. Two key questions are: how vulnerable will the GBR be to future environmental scenarios, and to what extent can local management actions lower vulnerability in the face of climate change? To address these questions, we use a simple empirical and mechanistic coral model to explore six scenarios that represent plausible combinations of climate change projections (from four Representative Concentration Pathways, RCP s), cyclones and local stressors. Projections (2017–2050) indicate significant potential for coral recovery in the near‐term, relative to current state, followed by climate‐driven decline. Under a scenario of unmitigated emissions ( RCP 8.5) and business‐as‐usual management of local stressors, mean coral cover on the GBR is predicted to recover over the next decade and then rapidly decline to only 3% by year 2050. In contrast, a scenario of strong carbon mitigation ( RCP 2.6) and improved water quality, predicts significant coral recovery over the next two decades, followed by a relatively modest climate‐driven decline that sustained coral cover above 26% by 2050. In an analysis of the impacts of cumulative stressors on coral cover relative to potential coral cover in the absence of such impacts, we found that GBR ‐wide reef performance will decline 27%–74% depending on the scenario. Up to 66% of performance loss is attributable to local stressors. The potential for management to reduce vulnerability, measured here as the mean number of years coral cover can be kept above 30%, is spatially variable. Management strategies that alleviate cumulative impacts have the potential to reduce the vulnerability of some midshelf reefs in the central GBR by 83%, but only if combined with strong mitigation of carbon emissions.